Stratigraphy and major paleoenvironmental changes in the Sea of Okhotsk during the last million years inferred from radiolarian data. - Matul, Alexander G; Abelmann, Andrea; Nürnberg, Dirk; Tiedemann, Ralf (PANGAEA, 2009)
Radiolarian distribution is studied in Core IMAGES MD01-2415 (46 m long) from the central Sea of Okhotsk. Obtained data made it possible to refine regional biostratigraphy and document the major paleoenvironmental changes in the basin during last million years. In total, 17 radiolarian datum planes are defined with 12 of them being new. Their number exceeds that previously established for different fossil groups in the Subarctic Pacific for this period. Radiolarian datum planes are usually confined to the main boundaries and Quaternary climatic events. Analysis of radiolaria distribution reveals several major paleoenvironmental shifts in the sea that occurred 950, 700, and 420-280 ka ago and are correlative with regional and global phases of the Middle Pleistocene climatic revolution.
Radiolarian datum planes in Core MD01-2415
Keywords: AGE; Archive of Ocean Data; ARCOD; DEPTH, sediment/rock; Giant piston corer; GPC; IMAGES VII - WEPAMA; Isotopic event; Marion Dufresne; MD012415; MD01-2415; MD122; Occurrence; Sea of Ochotsk; Species